Acknowledge the Past, Face the Present, Change the Future: Implementing Call to Action 93 in TESL Classrooms - Kinzie, Stephanie (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2023)
Call to Action 93 requests revision of the Canadian citizenship materials to include more information about treaties and residential schools. Although the citizenship materials have been analyzed in terms of how they present the concepts of citizenship, multiculturalism, and Canadian values, little work has been done on how Discover Canada (2012) presents the history of Indigenous peoples in Canada in relation to the Calls to Action. Discover Canada (2012) includes only one mention of the term “residential schools” and four mentions of the terms “treaty” or “treaties” in relation to Indigenous groups. Equally troubling, though, is the guide’s overall characterization of Indigenous groups and their history in Canada. By asking critical questions about textual features that fit into TESL curricula, I demonstrate how TESL instructors can both meet the language teaching requirements of their institutions and answer Call to Action 93 by presenting alternative narratives about Indigenous history in Canada.